(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Strongyloidiasis is a common parasitic disease in tropical and sub-tropical regions of the world. Infection with Strongyloides Stercoralis usually remains asymptomatic with peripheral eosinophilia and uncontrolled growth. Consequently, immunocompromised individuals are at a higher risk of complications of this disease. A case of an immunocompetent patient who had complaint of acute abdominal pain and was found to have duodenal ulceration. Laboratory examination revealed significantly elevated absolute eosinophil count at 17000/cmm (normal 0-500/cmm). The stool R/E revealed rhabtidiform larvae suggestive of Strongyloides stercoralis nematode. Endoscopy of upper GIT showed ulcer in duodenum. The patient was treated with weekly dose of Tab Albendazole for two weeks and after that peripheral eosinophilia count became normal. This study found that the elevated eosinophil count played a central role in the pathogenesis. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 109-111